O vilipêndio da COVID-19 em call e contact centres em Portugal - Isabel Roque (e-cadernos ces)
Since the end of the 1990s, call and contact centres in Portugal have been dealing with issues not only related to labor rights but also to workplace safety and health. With the outbreak of the COVID-19 pandemic, these locations became hotspots for outbreaks of the virus. Class inequalities were aggravated by the demarcation between essential and non-essential workers. After a state of emergency was formally declared, most call and contact centre operators moved to teleworking, suffering a significant loss of labor rights and an increase in pervasive control and surveillance, along with other psychosocial risks. Between March 2020 and May 2022, using a netnographic approach, in-depth interviews were conducted with call and contact centre operators and union members in Portugal to analyze the impacts of the pandemic and the transition to teleworking.